1991
DOI: 10.1023/a:1015879717742
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We describe the synthesis of new fluorotamoxifen analogues with the fluorine atom positioned on the end of the aliphatic chain of tamoxifen. The binding of fluorotamoxifens to cytosol estrogen receptors of rat uteri was determined with [3H]estradiol (5 nM). The fluorotamoxifens had similar or superior binding affinities compared with tamoxifen. The IC50 value was as follows: tamoxifen, 5 x 10(-7) M; fluorotamoxifen (VII), 5 x 10(-7) M; N,N-diethylfluorotamoxifen (IV)-cis, 1 x 10(-6) M, and trans, 2 x 10(-7) M;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Binding assays were carried out for selected compounds, representing highly potent members of their corresponding series. A novel radiolabeled estradiol displacement protocol was developed from existing studies. , ERα-rich cytosol isolated from rat uteri was used in the procedure. Binding affinity as determined by the K i value was measured for compounds 2a , 3a , 4d , and 5e and is illustrated (with reference to TAM) in Table .…”
Section: Biochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Binding assays were carried out for selected compounds, representing highly potent members of their corresponding series. A novel radiolabeled estradiol displacement protocol was developed from existing studies. , ERα-rich cytosol isolated from rat uteri was used in the procedure. Binding affinity as determined by the K i value was measured for compounds 2a , 3a , 4d , and 5e and is illustrated (with reference to TAM) in Table .…”
Section: Biochemistrymentioning
confidence: 99%
“…It has been suggested that building flexibility into the rigid backbone of antiestrogens could enhance their activity and binding affinity for the estrogen receptor , The chemotherapeutic and antiestrogenic potential of the compounds prepared is determined through appropriate biochemical assays. The availability of highly resolved crystal structure studies of the estrogen receptor α (ERα) allows the investigation of both actual and theoretical interactions of both estrogenic and antiestrogenic materials in the LBD. A thorough computational investigation of the predicted orientation and interaction of representative compounds within the LBD of the human ERα is undertaken, with a view to rationalizing antiestrogenic activity observed through analyzing ligand−receptor interactions, to provide an insight into the basis for biological activity of the compounds prepared . Such work further illustrates the eclectic liganding behavior of ERα and its tolerance for flexible antiestrogen systems.…”
Section: Introductionmentioning
confidence: 99%
“…To confirm our hypothesis that these compounds were acting through the estrogen receptor, an initial binding investigation ,, was carried out using compounds 7 and 15 as representative candidates. The study indicates the compounds are competitive antagonists with moderate binding affinity for the ER (binding K i 3.2 ± 2.1 μM ( 7 ) and 828 ± 106 nM ( 15 )), marginally weaker than that measured for tamoxifen ( 1 ) and the structurally related benzocycloheptenes .…”
mentioning
confidence: 99%